Solve -36 = j + 13 for j .
2 answers:
Answer:
J = -49
Step-by-step explanation:
Answer:
x=-49
Step-by-step explanation:
-36=j+13
first we need to get j by itself so we need to move 13 from the right side to left by subracting 13 from both sides.
-36-13=j+13-13
-49=j
since J is alone that is the answer
You might be interested in
Answer:
2a/b1 +b2=h
And
2a/h -b2=b1
Step-by-step explanation:
Answer:
27 units (whatever units the figure was measured in)
Step-by-step explanation:
Correct
m<2 = 125
m<8 = 55
m<14 = 100
m<16 = 80
Answer:
36.16
Step-by-step explanation:
A=a+b
2h=8.5+13.75
2·3.25=36.15625
Answer:
first choice..
first choice